The Theoretical Analysis of the Use of Micropiles as Load-Recovering Elements via the Poulos and Davis Methodology - Amado-León, Emerson; Rodriguez-Rincón, Edgar (Ingeniería, 2025)
Context: Micropiles have been mainly employed as soil reinforcement or supporting elements. As load-recovering elements, they have been used in pile groups where one of the elements has turned out to be defective or incomplete. This type of use has not been directly reported in the literature, so it is important to generate knowledge about the conditions to be considered when evaluating the use of micropiles as replacements for defective piles. Method: This research verified and described the settlement behavior and load distribution of both piles and micropiles for five proposed models. The results were obtained through the analytical methodology by Poulos and Davis for pile group settlement, analyzing the influence of three variables on micropiles: position in the cap area, spacing, and quantity. Results: The load distribution in the micropiles showed greater uniformity as their number increased. Likewise, a load increase was observed as the distance between the micropiles and the upper left corner of the cap decreased. With greater spacing and micropile count, the settlements decreased. Conclusions: In order to use micropiles as load-recovering elements in existing foundations, it is convenient to consider variables such as quantity, position, and spacing, as they influence both the load distribution and the settlements of the structure.